Comparative analysis of police dictatorships in Portugal and Spain - Irene Flunser Pimentel (Ибероамериканские тетради, 2023)
From 1932 onwards, with the arrival of the presidency of the Council of Portugal, António Oliveira Salazar created a new regime of civil dictatorship, which had both similarities and differences with the fascist regime in Italy and the National Socialist regime in Germany. The main similarity of these political regimes was the aggressive activity of the secret state police. In this study, the author will try, in its first part, to make a comparative study between the PVDE (Polícia de Vigilância e Defesa do Estado - State Surveillance and Defense Police, 1933-1945) and the political police apparatus of fascist Italy, nationalsocialist Germany and Franco’s dictatorship in Spain during World War II. With the defeat of Fascism and Nazism, two dictatorial regimes remained in the Iberian Peninsula, whose political police were related to each other. In a second part of this article the author compares Portuguese PIDE (Polícia Internacional de Defesa do Estado - Portuguese International Police, 1945-1969) and later DGS (Drirecção-Geral de Segurança - Directorate-General of Security, 1969-1974), on the one hand, and Spanish Seguridad (Dirección-General de Seguridad - Directorate-General for Security), on the other.